The Gutenberg parenthesis the age of print and its lessons for the age of the internet - Jarvis, Jeff 1954- (Bloomsbury Academic, 2023)
"To help us understand our transition out of the Gutenberg Age, Jeff Jarvis presents a history of print and its technologies – of its spread, of print inventions such as the modern novel, the essay, the newspaper, and of attempts to control speech through censorship and copyright. The five-century-long age of print was a grand exception in history. It gave rise to a worldview which some call print culture – shaped according to the completeness, permanence, materiality, authorship, and authority of text. As print and its influence on every aspect of life is now eclipsed by new technologies – the internet and data – the contrast between these eras gives us the opportunity to better understand print’s presumptions. This captivating, profound, challenging, and ultimately optimistic saga contends that we are returning to a time before mass media, to a society built on conversation, and that we are relearning how to hold that conversation with ourselves. Drawing upon the work of scores of scholars in book history, technology, sociology, religion, literature, law, media, and design, The Gutenberg Parenthesis examines print’s age on a grand scale and challenges readers to learn its lessons as we design the internet and society of our future [...]."
Includes bibliographical references and index
Keywords: Buchdruck; Druckmedien; Geschichte; Printing / History